Community Empowerment through Sustainable Green Waste Bank Bandung City - Naufal Fajri; Nike Kamarubiani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2002)
The waste bank is a local institution that was formed with public concern to create a clean environment and avoid various kinds of infectious diseases. Waste banks play an important role in providing education for the community to manage their waste from their respective homes so that it will form a new habit in overcoming waste problems. In addition, the waste bank has the value of developing the people’s economy which has a significant impact on the welfare of the community. With the existence of a waste bank, people can save their waste and then exchange it for a predetermined amount of money so that it can be useful for their daily needs. In this study, the method applied is a qualitative descriptive method. The results of this study indicate that community empowerment through the Hijau Lestari Waste Bank in Cicaheum Village, Kiaracondong District, Bandung City can be realized through two stages of activities including socialization of managing waste from home and other supporting programs to create public awareness of the environment such as gardening programs, waste recycling programs, and a program for processing waste into organic fertilizer.